2007
DOI: 10.1099/vir.0.83108-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene-expression profiles of a hepatitis B small surface antigen-secreting cell line reveal upregulation of lymphoid enhancer-binding factor 1

Abstract: The genome of hepatitis B virus (HBV) consists of four open reading frames, encoding the envelope proteins (Pre-S/S), the core proteins (Pre-C/C), the polymerase (P) and the transactivating X protein (X). In the sera of HBV-infected patients, hepatitis B surface antigen (HBsAg) particles without the viral genome can outnumber virions by more than 1000-fold. To analyse the interactions between HBsAg and host cells, global gene-expression profiles of a small HBsAg (SHBs)-secreting stable cell line (HepG2-S-G2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…26,28 It was demonstrated that HBsAg could stimulate proliferation and functional modification of hepatocytes via lymphoid enhancer-binding factor 1 through the Wnt pathway at the pre-malignant stage. 29,30 Taken together, these data suggested that higher expression of HBsAg could promote malignant transformation in hepatocytes via direct or indirect effect on many cellular functions, which was consistent with the epidemiological observation of a higher risk of HCC in patients with increasing levels of HBsAg in present study.…”
Section: Cancer Epidemiologysupporting
confidence: 91%
“…26,28 It was demonstrated that HBsAg could stimulate proliferation and functional modification of hepatocytes via lymphoid enhancer-binding factor 1 through the Wnt pathway at the pre-malignant stage. 29,30 Taken together, these data suggested that higher expression of HBsAg could promote malignant transformation in hepatocytes via direct or indirect effect on many cellular functions, which was consistent with the epidemiological observation of a higher risk of HCC in patients with increasing levels of HBsAg in present study.…”
Section: Cancer Epidemiologysupporting
confidence: 91%
“…Other HBV proteins linked to Wnt include the core (HBcAg) protein shown to bind to 41 Wnt pathway gene promoters, although functional effects remain unproven , and HBsAg that has been shown to upregulate LEF‐1, CCND1 and MYC in vitro . Other studies linking HBV to Wnt report upregulated DVL3 , upregulation of Wnt1 protein on HBV infected HCC patients (20) and upregulation of Wnt3a and FZD7 in HBV associated HCC samples (21).…”
Section: Viruses Implicated In Human Cancer Developmentmentioning
confidence: 99%
“…By microarray study of cells transfected with the S gene coding for HBsAg, we have previously shown that marked up-regulation of lymphoid enhancer-binding factor 1 (LEF-1), a transcriptional factor in Wnt pathway, was closely correlated with HBsAg expression [ 10 ]. Furthermore, the expression level and cellular distribution of LEF-1 protein, mainly the dominant negative truncated isoform, was changed by the expression of HBsAg.…”
Section: Introductionmentioning
confidence: 99%